Psychological Peculiarities of Personal Interethnic Communication - Kykhtuik, Oksana (Psychological Prospects Journal, 2015)
The article is focused on the main theoretical approaches to the concept of communication, psychological characteristics of communication. Communication barriers are considered as conventional impediments that may arise during the com- munication process. Psychological features of tolerance, ethnic and communicative tolerance viewed as phenomena of interpersonal interaction have been studied. The theoretical and empirical study revealed the relationship between ethnic tolerance and communication tolerance. Both kinds of tolerance affect professional and personality spheres of an individual future life. The study showed a significantly negative correlation with individual depression, shyness, motivation to avoid failure. However, positive correlation was observed between the rates of ethnic tolerance and commu- nication skills, conceptual thinking, motivation for success. Thus the idea that the specificity of interethnic communication is associated with ethnic and communicative tolerance, human inner states and properties has been confirmed. The introduced educational, psychological and pedagogical programme, which takes into account person’s cognitive, emotional and motivational features, aims at developing individual tolerance.